The role of parenting patterns in early childhood emotional regulation in the digital era - Amali, Nailul; Hikmah, Fitrotul (Thufuli, 2025)
The digital era introduces challenges to the emotional development of young children as a result of heightened media exposure. Parents significantly influence the regulation of their child's emotions. The parenting style significantly influences this issue. This study seeks to examine the different parenting styles that affect children's emotional development. This study employs a literature review methodology. The literature database was accessed via Google Scholar.  Data were gathered through literature searches using the terms "parenting method," "emotion regulation," "early childhood," and "digital media.". Synthesizing findings from multiple studies to examine the impact of various parenting styles—democratic, permissive, and authoritarian—on children's emotional development. The findings demonstrate that democratic parenting, defined by open communication and emotional support, significantly improves children's emotional regulation, whereas authoritarian and permissive parenting styles may impede emotional development. This study highlights the necessity for parents to adapt their parenting strategies in response to children's exposure to digital media, thereby effectively supporting their emotional development.